Securing Environmental Flows Through System Reoperation and Management: Lessons From Case Studies of Implementation - Opperman, Jeffrey J.; Kendy, Eloise; Barrios, Eugenio (Frontiers in Environmental Science, 2019)
Water-management infrastructure, such as dams, diversions, and levees, provides important benefits to society, including energy, flood management, and water supply, but this infrastructure is a primary cause of the decline of freshwater ecosystems and the services they provide. Due to these declines, recent attention has focused on improving the environmental performance of water infrastructure, such as modifying the location, design, or operation of infrastructure to maintain or restore environmental flows. Despite growing attention to the importance of environmental flows, and continued advancement in flow assessment methods, implementation of flow protection or restoration has lagged expectations. In this paper we describe how pursuing environmental flows at the scale of infrastructure systems, rather than individual sites, such as a dam, offers two pathways to increased implementation of environmental flows. First, policy and management mechanisms that apply to large areas—river basins or political jurisdictions—can catalyze large-scale implementation of flow protection or restoration. We provide two examples of system-scale policy and management mechanisms: flow protection policies and system-scale hydropower planning and management. Although system-scale policy and management offer a clear path to large-scale implementation, there will continue to be a need for flow implementation that occurs at smaller scales, such as a high priority river reach. The second pathway focuses on implementation at that scale—such as environmental flow releases from a dam or small set of dams—but embeds dam reoperation or site-scale flow implementation within reoperation of the larger systems of resource management within which the dam or ecosystem is located. These systems of resource management can encompass various sectors and here we provide examples of dam reoperation or flow implementation facilitated by solutions that included changes to the management of (1) water supply systems; (2) floodplains; and (3) irrigation systems. We illustrate both of these system-scale pathways through a set of case studies, drawn primarily from North America, each of which includes an example of current implementation.